Correlation between level of adipocytokines with body composition and heart rate recovery indices - Ristić, Marko A.; Đelić, Marina (Medicinski podmladak, 2020)
Introduction: Adipose tissue as an endocrine organ primarily regulates metabolism of carbohydrates and lipids. Anorexigenic hormone leptin increases sympathetic activity and decreases insulin secretion, thereby reducing energy depots, while adiponectin elevates tissue sensitivity to insulin, which role visfatin imitates. Heart rate recovery index(ΔHRR), linked with insulin resistance syndrome, reflects parasympathetic function. Our goal was to analyze correlation between adipocytokines with body composition and ΔHRR in athletes and sedentary controls.Material and methods: Research included 19 volleyball and water polo national team members (mean age 19.26±1.94years) and 13 physically inactive male students (mean age 20.46±1.13 years). Anthropometric data were measured and blood samples for hormone analysis were taken: at the beginning, the end and 30 minutes after finishing ergospirometry. Statistical evaluation was performed using: Student’s t-test, Mann-Whitney, Wilcoxon’sand Spearman’s rank correlation test.Results: Adiponectin levels between dependent and independent variables didn’t show statistical significance. Leptin level, noteworthy lower in athletes at the beginning and the end of the test (p